The CoViD-19 Pandemic and the End of Corporate Risk Management as we know it - Markus Will (The Central European Review of Economics and Management (CEREM), 2020)
Aim: The article is intended to contribute to a discussion on risks related to the CoViD-19 pandemic, which was started in the last issues of this journal. Findings: The article discusses the thesis that conventional risk management is reaching its limits in its application in companies, particularly with regard to low-probability but high-impact events its applications seems nor appropriate. In complex and tightly coupled systems like global supply chains, catastrophic events must be considered "normal". The risk of a global pandemic is well known, and at the end of 2019 the first signs of an impending outbreak were also evident. Nevertheless, the global pandemic and the gradual lockdown was surprising in that no precautionary measures were taken. Therefore, this paper argues for a change of perspective from traditional risk management to BCM and for increasing the resilience of supply chains.
Keywords: 330; CoViD-19; risk management; black swans; business continuity; supply chain resilience